Progressive skills in English 2 : listening and speaking : course book - Phillips, Terry; Phillips, Anna (Reading : Garnet Education, 2012)
Progressive Skills in English Level 2: Listening and Speaking is part of a dynamic four-level academic course designed to equip students with the essential skills for university-level study in English. This edition specifically builds the skills required for active participation in lectures and tutorials. It focuses on critical listening strategies, note-taking techniques, and effective academic speaking, including giving presentations and engaging in seminar discussions. Through academic-themed units, it provides a structured pathway for students to transition from general language proficiency to successful academic research and interaction.
"Prepares students for entry into English-medium study"--Cover.
Keywords: English language -- Textbooks for foreign speakers; Listening -- Study and teaching (Higher).; Public speaking -- Study and teaching (Higher).; English language -- Spoken English